Biocontrol of Listeria monocytogenes and Salmonella Typhimurium in hydroponics: Evaluating the efficacy of plant growth promoting bioinoculants - Grace Akumu; Leslie D. Thompson; Mindy M. Brashears; Catherine R. Simpson; Christopher J. Currey; Angela M. Walla (Food Control, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Mass timber wall splice connection using glued-in rods: Design methodology, implementation, and shake-table testing in a six-story building - Steven Kontra; Andre R. Barbosa; Arijit Sinha; Steve Pryor; Reid B. Zimmerman; Barbara Simpson; John W. van de Lindt; Shiling Pei; Gustavo A. Araújo R.; Morgan McBain; Ludovica Pieroni; Prashanna Mishra; et al. (Engineering Structures, 2026)

Fire–Moisture Interactions Shape Recovery Trajectories Across Temperate Vegetation Communities - Emily K. Simpson; Glenda M. Wardle; Christopher R. Dickman; Aaron C. Greenville (Global Change Biology, 2026)
The recovery of vegetation following fire is increasingly shaped by concurrent climate‐driven hydrological extremes, such as drought and extreme precipitation. Under these multi‐disturbance scenarios vegetation communities are likely to show different recovery thresholds and trajectories of change, but this is yet to be fully understood or quantified. We used the Greater Blue Mountains World Heritage Area in south‐eastern Australia as a model system to assess how sustained moisture surplus or deficit could differentially influence the recovery of forest, heath and wetland vegetation from low‐extreme severity fire. From 2015 to 2024, this region experienced severe drought, extensive bushfires (the ‘Black Summer’ bushfires) and extreme rainfall events. By using a new remote‐sensing index (the Post‐fire Stability Index) that measures the rate of change in a disturbed system, we found that most vegetation communities could recover following low‐severity fire even in the case of poor soil moisture conditions, but moisture became increasingly limiting as burn severity increased. Certain communities, such as wet sclerophyll forests and freshwater wetlands, experienced disproportionate declines (up to times greater than other communities) as burn severity and drought intensified. These communities are likely at greatest risk as climate drying escalates. We stress that future recovery from fire in temperate communities will be governed not only by the characteristics of the fire itself and those of the affected vegetation community, but also by the extent to which these characteristics interact with prevailing hydro‐climatic conditions.

The closer, the better: intratumoral delivery of a thermoresponsive gemcitabine-loaded hydrogel in preclinical PDAC models - Andrea Vallés-Martí; Ajinkya Manelkar; Christopher R. Simpson; Priscilla Kinderman; Eveline de Jonge-Muller; Anthea van der Wielen; Stefanus G.T. Janson; Ahmad Alrawahneh; Li Zihao; Tushar Tomar; Mike G.W. de Leeuw; Helena M. Kelly; et al. (Drug Delivery and Translational Research, 2026)

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

How Implementing the Rights of Wetlands Provides Benefits to People and Wetlands: Relationships, Rights, Responsibilities, Experiences, and Actions - Gillian Davies; Ritesh Kumar; M. Siobhan Fennessy; Nick Davidson; Kai Huschke; Dave Pritchard; Matthew Simpson; Priyanie Amerasinghe; William R. Moomaw; Erin Okuno; Bethanie Walder; Chaturangi Wickramaratne; et al. (Wetlands, 2026)
Rights of wetlands shifts the people-wetlands relationship towards one recognizing the intrinsic rights and living beingness of wetlands, embodying reciprocity, kinship, and gratitude. Recognition of wetland rights occurs within the broader Rights of Nature movement, which has often been led by Indigenous Peoples and local communities from many cultural traditions. Intrinsic wetland rights centre on the right to exist and incorporate seven other rights, forming a holistic framework that enables preservation of wetland ecosystem integrity. These rights provide the basis for a wetland’s thriving existence. The eight rights are: • the right to exist. • their natural place in the landscape; • natural and connected hydrologic regimes; • natural climatic conditions; • naturally occurring biodiversity; • natural ecosystem processes; • natural water, soil, and air quality (i.e., structural integrity and form); and. • regeneration and a naturally determined future. Moral and ethical responsibilities towards these rights include fostering harmonious relationships in and with wetlands, respecting interdependence of all wetland components, safeguarding and fostering conditions enabling rights of wetlands, and acting in a precautionary manner when faced with risks of harm to wetlands. Legal and policy responsibilities include acknowledging plural worldviews, recognising legal standing and political orientations to represent and defend wetland rights, providing adequate means for wetland representation and defending and advocating for wetlands, and using best available science to restore degraded wetlands and support regeneration, thereby supporting harmonious societal relationships with wetlands. Opportunities for implementation of rights of wetlands at a variety of scales (individual, community, national, and global) are explored, and training/guidance resources are referenced.

Assessing the potential impact of environmental land management schemes on emergent infectious disease risks - Christopher J. Banks; Katherine Simpson; Nick Hanley; Rowland R. Kao (Journal of Environmental Management, 2026)

High incidence of estrous cycle irregularities in heterogeneous stock (HS) rats is associated with footshock-resistant cocaine intake - Elizabeth A. Sneddon; Supakorn Chonwattanagul; Kathleen Bai; Pranav H. Kurup; Sonja L. Plasil; Michelle R. Doyle; Sélène Zahedi; Sierra Simpson; Benjamin C. Sichel; Dyar N. Othman; Molly Brennan; Abraham A. Palmer; et al. (Psychopharmacology, 2026)
Rationale Hormonal fluctuations throughout the estrous cycle are hypothesized to influence drug-related behaviors. Preclinical models show that some cocaine-related behaviors are influenced by the estrous cycle. However, the extent to which the estrous cycle modulates cocaine self-administration in outbred heterogeneous stock (HS) rats is unknown. Objectives We aimed to examine the relationship between estrous phases and cocaine self-administration behavior in HS rats using an operant model of extended access to cocaine self-administration. Methods We assessed the escalation of intake, breaking point, and resistance to foot shock. Using vaginal swabbing and lavage techniques, we characterized the relationship between estrous phase and cocaine behaviors. We then comprehensively evaluated estrous cycling patterns in young adult and adult HS rats, comparing them with Wistar rats. Results Estrous phase showed no association with cocaine self-administration in HS rats. 82% of female HS rats exhibited irregular estrous cycling with variability to the phase length, even in the absence of drug exposure, a phenomenon not observed in the Wistar strain. Females with irregular cycling showed greater footshock-resistant cocaine intake. Conclusions This study provides the first evidence that most female HS rats exhibit irregular estrous cycling. In HS rats, the estrous phase per se has no major influence on cocaine self-administration, whereas cycling irregularity was associated with specific addiction-related behaviors, including footshock-resistant intake. As HS rats gain popularity in behavioral and genome-wide studies, understanding these cycle disruptions is crucial as they may reveal genetic links into cycling variability and individual differences to aspects of cocaine use.

When a mosquito ingests blood, the phagocytic activity of hemocytes increases with warmer environmental temperature and aging - Jordyn S. Barr; Saksham R. Saksena; Abby Callahan-Muller; Edith Simpson; Julián F. Hillyer (Journal of Invertebrate Pathology, 2026)

Surface characteristics limit the vertical mobility of an invasive reptile - Thomas W. Simpson; Marleen Baling; Anne C. Gaskett; Richard C. Gibson; Steven Matthews; Jacqueline R. Beggs (Biological Invasions, 2026)
Preventing the spread of small, cryptic invasive reptiles poses an ongoing challenge for conservation and biosecurity worldwide. Physical exclusion barriers offer a potentially low-cost, non-toxic tool for limiting dispersal, but their effectiveness depends on, among other factors, a detailed understanding of how surface properties influence animal movement. We tested four commonly available fencing materials—polypropylene fabric, woven polypropylene, polythene sheet, and acrylic sheet—as potential barriers to climbing by a small Australian skink, Lampropholis delicata (Scincidae). Experiments with 18 adult skinks were conducted in enclosures under both wet and dry conditions. We quantified surface roughness using four metrics: arithmetic average roughness (Ra), total height of profile (Rt), mean spacing of profile irregularities (Rsm) and Skewness (Rsk). Climbing frequency was highest on the roughest material, polypropylene fabric (Ra = 25, Rt = 167, Rsm = 457.5 µm), with up to 60% of individuals climbing. In contrast, the smoother surfaces, polythene and acrylic, limited climbing to just 5% of trials, with climbs occurring only under wet conditions. This suggests that surface water may enhance adhesion and reduce the effectiveness of smooth barriers. Our findings indicate that simple vertical drift fences are unlikely to effectively manage the spread of L. delicata , particularly in wet environments and underscore the importance of incorporating surface roughness thresholds and moisture conditions into barrier design. Polythene sheet, shows promise for indoor containment but would require modifications such as anti-climb lips for outdoor use. Tailored exclusion strategies that integrate material science with animal behaviour and ecological context could offer scalable, environmentally friendly tools for containing and managing invasive species.

Assessing behavioural economic demand for morphine after an acute dose in individuals with- and without childhood trauma: a double-blind, randomised, controlled trial - Martin Trøstheim; Benjamin L. Berey; Elizabeth R. Aston; Matthew J. Gullo; Lee Hogarth; Graham Simpson; Rupert Broomby; Celia J. Morgan; Molly Carlyle (Psychopharmacology, 2025)
Background Childhood trauma is associated with positive subjective responses to acute opioids in the laboratory. Yet, its impact on behavioural economic demand for opioids remains unclear. Because demand can predict future use and misuse, we investigated whether individuals with childhood trauma also display greater demand for opioids in the laboratory. Methods This secondary analysis used data from a double-blind, randomised, controlled, counterbalanced trial. Across two sessions, individuals with ( n = 26) and without ( n = 21) childhood trauma received a high (0.15 mg/kg) and low (0.01 mg/kg) dose of intramuscular morphine 120 min before a hypothetical purchase task. Participants also regularly reported their subjective desire for the study drug. Area under the consumption and expenditure curves, and specific demand indices ( O max , P max , breakpoint , intensity , elasticity ), were analysed with non-parametric mixed models. Results Consumption and expenditure for low dose morphine was lower in the childhood trauma group when compared to high dose morphine in this group, and low dose morphine in the control group ( p s ≤ 0.03). Consistent results were obtained for specific demand indices O max , P max , and breakpoint , but not intensity or elasticity . Positive correlations between subjective desire and consumption and expenditure were only observed in the childhood trauma group ( Tau-c = 0.24–0.34, p s ≤ 0.03). Conclusion Under laboratory conditions, desires to use opioids among individuals with childhood traumas may not manifest in strong intentions to acquire these drugs. Diverging results from psychometric measures of subjective and economic opioid value highlight the need for future research to explore contextual and resilience factors to understand how problematic opioid use emerges after childhood traumas.

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Microscale analysis of the fish Knightia eocaena taphonomy: Implication of a preserved microbial community - Garrett A. Rogers; Dakota R. Pittinger; Edward L. Simpson; Kurt Friehauf (Palaeobiodiversity and Palaeoenvironments, 2025)
Microbial communities are important components controlling the fidelity of fossil fish preservation. The Eocene Green River Formation lagerstätten, exceptionally preserved fossil deposits, provides an opportunity to examine the role of microbial communities and their metabolic byproducts, such as chemical precipitated in this spectacularly preserved fish deposit, famous throughout the world. Field emission scanning electron microscope (FESEM) and energy dispersive spectroscopy system (EDS) examination of a well-preserved Knightia eocaena from the Eocene Green River Formation documents the presence of bacteriomorphs. Bacteriomorphs in a sample from the Fossil Butte Member of the Green River Formation consists of spherical structures, coccoid-type bacteria, fibres from two-sized populations of filamentous bacteria, probable filamentous cyanobacteria, capsule-shaped, and bacilliform bacteria, all associated with framboidal iron hydroxide. Bacteriomorphs consist of external molds composed of nanometer-scale calcium carbonate spheres. Fe-oxide framboids have an amorphous exterior and a sieve-like internal structure. The sieve-like structure consists of nanometer-scale pores, probable sites of bacterial cells with walls composed of 100-nanometer-scale spheres. Fe-oxides are consistent with bacterially mediated precipitation of pyrite followed by an oxidation event. Preserved bacteriomorphs are consistent with degradation of soft tissue, limiting the preservation of soft tissue and leaving bone and scales with no appreciable soft tissue. The microfossils are restricted to the skeleton and are not found in the surrounding rock matrix, suggesting larger microbial mats may not have been present and possibly did not have a significant impact on the preservation of this specimen.

New Approach Needed To Address Declining Forestry Research Capacity And Relevancy in the US: A Call-To-Action - Robert G. Wagner; Alexander L. Friend; Emily J. Silver; Julio Rojas; Thomas R. Fox; Terry Baker; Robert Simpson (Journal of Forestry, 2025)
Recent dramatic reductions in research funding and personnel for university and government organizations by the new federal administration will reduce forestry research capacity in the coming years. However, these cuts only highlight the long-standing decline in forestry research capacity that has been occurring over the past several decades. These reductions will continue to impair the country’s ability to meet the scale and complexity of challenges facing US forests. At some point in the future, there will be an opportunity to rebuild and reshape forestry research capacity to address these challenges. Now is the time to plan the future of forestry research. Successfully rebuilding this capacity will require national support from a broad coalition of forest management organizations. Receiving this support will require substantially increasing the relevancy of research to forest managers relative to what has occurred in recent decades. We offer several suggestions for this rebuilding effort, including: 1) developing a periodic national survey of forest managers to clearly identify the most important problems they face on the ground, 2) regularly communicating results of the survey to forest researchers, program leaders of research funding agencies, policy makers, legislators, and others responsible for allocating forest research effort and funding, and 3) building on the science delivery successes of stakeholder-driven organizations such as the forest manager / university research cooperatives around the country.

Optimising behind-the-meter solar for water distribution systems: impact of network configuration and electricity tariff structure - Qi Zhao; Wenyan Wu; Angus R. Simpson (Journal of Cleaner Production, 2025)

Implications of improved remote sensing capabilities on blue carbon quantification - Steven W.J. Canty; Miguel Cifuentes-Jara; Jorge Herrera-Silveira; Hannah K. Morrissette; Jordan R. Cissell; Joanna Acosta-Velázquez; Emil Cherrington; Ilka C. Feller; Daniel A. Friess; Jonathan S. Lefcheck; Loraé T. Simpson; Claudia Teutli-Hernandez (Estuarine, Coastal and Shelf Science, 2025)

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Effects of macro vs. micro initialization and ocean initial-condition memory on the evolution of ensemble spread in the CESM2 large ensemble - Clara Deser; Who M. Kim; Robert C. J. Wills; Isla R. Simpson; Steve Yeager; Gokhan Danabasoglu; Keith Rodgers; Nan Rosenbloom (Climate Dynamics, 2025)
“Single Model initial-condition Large Ensembles” (SMILEs) conducted with Earth system models have transformed our ability to quantify internal climate variability and forced climate change at local and regional scales. An important consideration in their experimental design is the choice of initialization procedure as this influences the duration of initial-condition memory, with implications for interpreting the temporal evolution of both the ensemble-mean and ensemble-spread. Here we leverage the strategic design of the 100-member Community Earth System Model version 2 (CESM2) SMILE to investigate the dependence of ensemble spread on the method of initialization (micro- vs. macro- perturbations) and the effects of ocean initial-condition memory. We find that the evolution of ensemble spread in 10-year low-pass filtered data is relatively insensitive to the method of initialization beyond the second decade, with the notable exception of the tropical Indo-Pacific in the 4th decade, when macro-initialization significantly enhances ensemble spread, possibly as a result of a state-dependent response to major volcanic activity. Initial-condition memory associated with the chosen Atlantic Meridional Overturning Circulation (AMOC) states unfolds in two stages: First, in the North Atlantic lasting 4–5 decades, and subsequently, in the Indo-Pacific sector of the Southern Ocean appearing 35-years after initialization and lasting 3–4 decades. Known AMOC dynamics explain the first stage, but the role of AMOC and the mechanisms responsible for the delayed appearance of initial-condition memory in the Southern Ocean remain to be fully elucidated. Implications and recommendations for the design of future SMILEs are provided.

An evaluation of the seasonal Caribbean hydroclimate in low and high-resolution CESM and other CMIP6 models - Carlos J. Martinez; Isla R. Simpson; John T. Fasullo; Andreas F. Prein (Climate Dynamics, 2025)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Ice-marginal volcanic sequence in Iceland found on a nondescript gradual hillslope: An unexpected record of ice thickness late in deglaciation - Audrey R. Putnam; Kirsten L. Siebach; Candice C. Bedford; Sarah L. Simpson; Michael T. Thorpe; Joseph J. Tamborski; Elizabeth B. Rampe (Journal of Volcanology and Geothermal Research, 2024)

The role of dissolved organic carbon in Great Smoky Mountains National Park streams impacted by long-term acid deposition - Jason R. Brown; John S. Schwartz; Michael E. Essington; Qiang He; Matt A. Kulp; Ian M. Simpson (Environmental Monitoring and Assessment, 2024)

Measuring the Response Diversity of Ecological Communities Experiencing Multifarious Environmental Change - Francesco Polazzo; Romana Limberger; Frank Pennekamp; Samuel R. P.‐J. Ross; Gavin L. Simpson; Owen L. Petchey (Global Change Biology, 2024)
The diversity in organismal responses to environmental changes (i.e., response diversity) plays a crucial role in shaping community and ecosystem stability. However, existing measures of response diversity only consider a single environmental variable, whereas natural communities are commonly exposed to changes in multiple environmental variables simultaneously. Thus far, no approach exists to integrate multifarious environmental change and the measurement of response diversity. Here, we show how to consider and quantify response diversity in the context of multifarious environmental change, and in doing so introduce a distinction between response diversity to a defined or anticipated environmental change, and the response capacity to any possible set of (defined or undefined) future environmental changes. First, we describe and illustrate the concepts with empirical data. We reveal the role of the trajectory of environmental change in shaping response diversity when multiple environmental variables fluctuate over time. We show that, when the trajectory of the environmental change is undefined (i.e., there is no information or a priori expectation about how an environmental condition will change in future), we can quantify the response capacity of a community to any possible environmental change scenario. That is, we can estimate the capacity of a system to respond under a range of realistic or extreme environmental changes, with utility for predicting future responses to even multifarious environmental change. Finally, we investigate determinants of response diversity within a multifarious environmental change context. We identify factors such as the diversity of species responses to each environmental variable, the relative influence of different environmental variables and temporal means of environmental variable values as important determinants of response diversity. In doing so, we take an important step towards measuring and understanding the insurance capacity of ecological communities exposed to multifarious environmental change.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Challenges to Seagrass Restoration in the Indian River Lagoon, Florida - Vivienne A. Main; Morgan K. Gilligan; Sarah M. Cole; Todd Z. Osborne; Ashley R. Smyth; Loraé T. Simpson (Journal of Marine Science and Engineering, 2024)
Seagrasses provide valuable ecosystem services, including improved water quality, carbon sequestration, and sediment stabilization. Unfortunately, these critical habitats are declining globally due to a range of anthropogenic impacts. Restoration practitioners have made efforts to mitigate loss through the introduction of seagrass transplants. However, seagrass restoration has low success rates and is plagued by water quality concerns and ecosystem degradation. Studies to improve seagrass restoration efforts have targeted different functional taxa to allow for greater stability and recovery of threatened ecosystems, and excluded macro-grazers to limit losses to newly established and restored seagrasses. We hypothesized greater seagrass (Halodule wrightii) health when restored in conjunction with hard clams (Mercenaria mercenaria) and protected from grazers using herbivore exclusion devices (HEDs) in the Indian River Lagoon (IRL), Florida. While our study experienced high rates of seagrass mortality, we were able to observe significant differences in seagrass health between IRL sub-lagoons and observed the positive effects of HEDs on seagrass health. The observed high species mortality highlights how restoration in the IRL is hindered by biotic and abiotic stressors, site selection, and a lack of clear restoration protocols. As we see ongoing declines in water quality and loss of foundational species, informed site selection, greater understanding of grazer presence, and multi-species restoration will provide an informed approach for future seagrass restoration projects globally.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Response of Root Respiration to Warming and Nitrogen Addition Depends on Tree Species - T. J. Muratore; M. A. Knorr; M. J. Simpson; R. B. Stephens; R. P. Phillips; S. D. Frey (Global Change Biology, 2024)
Roots contribute a large fraction of CO 2 efflux from soils, yet the extent to which global change factors affect root‐derived fluxes is poorly understood. We investigated how red maple ( Acer rubrum ) and red oak ( Quercus rubra ) root biomass and respiration respond to long‐term (15 years) soil warming, nitrogen addition, or their combination in a temperate forest. We found that ecosystem root respiration was decreased by 40% under both single‐factor treatments (nitrogen addition or warming) but not under their combination (heated × nitrogen). This response was driven by the reduction of mass‐specific root respiration under warming and a reduction in maple root biomass in both single‐factor treatments. Mass‐specific root respiration rates for both species acclimated to soil warming, resulting in a 43% reduction, but were not affected by N addition or the combined heated × N treatment. Notably, the addition of nitrogen to warmed soils alleviated thermal acclimation and returned mass‐specific respiration rates to control levels. Oak roots contributed disproportionately to ecosystem root respiration despite the decrease in respiration rates as their biomass was maintained or enhanced under warming and nitrogen addition. In contrast, maple root respiration rates were consistently higher than oak, and this difference became critical in the heated × nitrogen treatment, where maple root biomass increased, contributing significantly more CO 2 relative to single‐factor treatments. Our findings highlight the importance of accounting for the root component of respiration when assessing soil carbon loss in response to global change and demonstrate that combining warming and N addition produces effects that cannot be predicted by studying these factors in isolation.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Recent and near‐term future changes in impacts‐relevant seasonal hydroclimate in the world's Mediterranean climate regions - Richard Seager; Yutian Wu; Annalisa Cherchi; Isla R. Simpson; Timothy J. Osborn; Yochanan Kushnir; Jelena Lukovic; Haibo Liu; Jennifer Nakamura (International Journal of Climatology, 2024)
Change over recent decades in the world's five Mediterranean Climate Regions (MCRs) of quantities of relevance to water resources, ecosystems and fire are examined for all seasons and placed in the context of changes in large‐scale circulation. Near‐term future projections are also presented. It is concluded that, based upon agreement between observational data sets and modelling frameworks, there is strong evidence of radiatively‐driven drying of the Chilean MCR in all seasons and southwest Australia in winter. Observed drying trends in California in fall, southwest southern Africa in fall, the Pacific Northwest in summer and the Mediterranean in summer agree with radiatively‐forced models but are not reproduced in a model that also includes historical sea surface temperature (SST) forcing, raising doubt about the human‐origin of these trends. Observed drying in the Mediterranean in winter is stronger than can be accounted for by radiative forcing alone and is also outside the range of the SST‐forced ensemble. It is shown that near surface vapour pressure deficit (VPD) is increasing almost everywhere but that, surprisingly, this is contributed to in the Southern Hemisphere subtropics to mid‐latitudes by a decline in low‐level specific humidity. The Southern Hemisphere drying, in terms of precipitation and specific humidity, is related to a poleward shift and strengthening of the westerlies with eddy‐driven subsidence on the equatorward side. Model projections indicate continued drying of Southern Hemisphere MCRs in winter and spring, despite ozone recovery and year‐round drying in the Mediterranean. Projections for the North American MCR are uncertain, with a large contribution from internal variability, with the exception of drying in the Pacific Northwest in summer. Overall the results indicate continued aridification of MCRs other than in North America with important implications for water resources, agriculture and ecosystems.

Drivers of population dynamics of at-risk populations change with pathogen arrival - Alexander T. Grimaudo; Joseph R. Hoyt; R. Andrew King; Rickard S. Toomey; Chris Simpson; Cory Holliday; Alexander Silvis; Rick T. Doyle; Joseph A. Kath; Mike P. Armstrong; Virgil Brack; Richard J. Reynolds; et al. (Biological Conservation, 2024)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Olfactory tract/bulb metal concentration in Manganese-exposed mineworkers - Luis F. Gonzalez-Cuyar; Gill Nelson; Susan Searles Nielsen; Wendy W. Dlamini; Amelia Keyser-Gibson; C. Dirk Keene; Michael Paulsen; Susan R. Criswell; Natalie Senini; Lianne Sheppard; Shar Samy; Christopher D. Simpson; et al. (NeuroToxicology, 2024)

Description and taxonomic assessment of fossil Cercopithecidae from the Pliocene Galili Formation (Ethiopia) - Hailay G. Reda; Stephen R. Frost; Evan A. Simons; Jay Quade; Scott W. Simpson (Journal of Human Evolution, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Monitoring the use of novel psychoactive substances in Australia by wastewater-based epidemiology - Emma L. Jaunay; Richard Bade; Kara R. Paxton; Dhayaalini Nadarajan; Daniel C. Barry; Yuze Zhai; Benjamin J. Tscharke; Jake W. O'Brien; Jochen Mueller; Jason M. White; Bradley S. Simpson; Cobus Gerber (Science of The Total Environment, 2024)

Anthropogenic, biogenic, and photochemical influences on surface formaldehyde and its significant decadal (2006–2017) decrease in the Lewiston-Clarkston valley of the northwestern United States - R. Li; B.T. Jobson; M. Wen; A.L. Li; Y. Huangfu; W. Zhang; R. Hardy; P. O'Keeffe; J. Simpson; M. Fauci; N. Paden (Chemosphere, 2024)

Sizing behind-the-meter solar PV for pumped water distribution systems: A comparison of methods - Qi Zhao; Wenyan Wu; Jiayu Yao; Angus R. Simpson; Ailsa Willis; Lu Aye (Journal of Cleaner Production, 2024)

Water distribution system design integrating behind-the-meter solar under long-term uncertainty - Jiayu Yao; Wenyan Wu; Angus R. Simpson; Behzad Rismanchi (Sustainable Cities and Society, 2023)

New computational tools and experiments reveal how geometry affects tissue growth in 3D printed scaffolds - Daniel J. VandenHeuvel; Brenna L. Devlin; Pascal R. Buenzli; Maria A. Woodruff; Matthew J. Simpson (Chemical Engineering Journal, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The distribution of metal and petroleum-derived contaminants within sediments around oil and gas infrastructure in the Gippsland Basin, Australia - Sharon E. Hook; Scott Foster; Franziska Althaus; Douglas Bearham; Brad M. Angel; Andrew T. Revill; Stuart L. Simpson; Joanna Strzelecki; Tom Cresswell; Keith R. Hayes (Marine Pollution Bulletin, 2023)

Improving the representation of groundwater processes in a large-scale water resources model - Helen Elizabeth Baron; Virginie D. J. Keller; R. Horan; Donald John MacAllister; Mike Simpson; Christopher R. Jackson; Helen A. Houghton-Carr; Nathan Rickards; Kaushal K. Garg; Muddu Sekhar; Alan MacDonald; Gwyn Rees (Hydrological Sciences Journal, 2023)

Improving the ecological and economic performance of agri-environment schemes: Payment by modelled results versus payment for actions - Katherine Simpson; Paul R. Armsworth; Martin Dallimer; Mary Nthambi; Frans P. de Vries; Nick Hanley (Land Use Policy, 2023)

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency - Shabnam Bakhshalizadeh; Daniella H. Hock; Nicole A. Siddall; Brianna L. Kline; Rajini Sreenivasan; Katrina M. Bell; Franca Casagranda; Sadishkumar Kamalanathan; Jayaprakash Sahoo; Niya Narayanan; Dukhabandhu Naik; Varun Suryadevara; et al. (Human Genetics, 2023)
Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp) shared by twin sisters presenting with POI, bilateral high-frequency sensorineural hearing loss, kidney and heart dysfunction. MRPL50 encodes a component of the large subunit of the mitochondrial ribosome. Using quantitative proteomics and western blot analysis on patient fibroblasts, we demonstrated a loss of MRPL50 protein and an associated destabilisation of the large subunit of the mitochondrial ribosome whilst the small subunit was preserved. The mitochondrial ribosome is responsible for the translation of subunits of the mitochondrial oxidative phosphorylation machinery, and we found patient fibroblasts have a mild but significant decrease in the abundance of mitochondrial complex I. These data support a biochemical phenotype associated with MRPL50 variants. We validated the association of MRPL50 with the clinical phenotype by knockdown/knockout of mRpL50 in Drosophila , which resulted abnormal ovarian development. In conclusion, we have shown that a MRPL50 missense variant destabilises the mitochondrial ribosome, leading to oxidative phosphorylation deficiency and syndromic POI, highlighting the importance of mitochondrial support in ovarian development and function.

Fine-scale variability in coral bleaching and mortality during a marine heatwave - Shreya Yadav; Ty N. F. Roach; Michael J. McWilliam; Carlo Caruso; Mariana Rocha de Souza; Catherine Foley; Corinne Allen; Jenna Dilworth; Joel Huckeba; Erika P. Santoro; Renee Wold; Jacquelyn Simpson; et al. (Frontiers in Marine Science, 2023)
Coral bleaching and mortality can show significant spatial and taxonomic heterogeneity at local scales, highlighting the need to understand the fine-scale drivers and impacts of thermal stress. In this study, we used structure-from-motion photogrammetry to track coral bleaching, mortality, and changes in community composition during the 2019 marine heatwave in Kāneʻohe Bay, Hawaiʻi. We surveyed 30 shallow reef patches every 3 weeks for the duration of the bleaching event (August-December) and one year after, resulting in a total of 210 large-area, high-resolution photomosaics that enabled us to follow the fate of thousands of coral colonies through time. We also measured environmental variables such as temperature, sedimentation, depth, and wave velocity at each of these sites, and extracted estimates of habitat complexity (rugosity R and fractal dimension D) from digital elevation models to better understand their effects on patterns of bleaching and mortality. We found that up to 80% of corals experienced moderate to severe bleaching in this period, with peak bleaching occurring in October when heat stress (Degree Heating Weeks) reached its maximum. Mortality continued to accumulate as bleaching levels dropped, driving large declines in more heat-susceptible species (77% loss of Pocillopora cover) and moderate declines in heat-tolerant species (19% and 23% for Porites compressa and Montipora capitata , respectively). Declines in live coral were accompanied by a rapid increase in algal cover across the survey sites. Spatial differences in bleaching were significantly linked to habitat complexity and coral species composition, with reefs that were dominated by Pocillopora experiencing the most severe bleaching. Mortality was also influenced by species composition, fractal dimension, and site-level differences in thermal stress. Our results show that spatial heterogeneity in the impacts of bleaching are driven by a mix of environmental variation, habitat complexity, and differences in assemblage composition.

Venom phenotype conservation suggests integrated specialization in a lizard-eating snake - Tucker C. Heptinstall; Jason L. Strickland; Ramses A. Rosales-Garcia; Rhett M. Rautsaw; Cassandra L. Simpson; Gunnar S. Nystrom; Schyler A. Ellsworth; Michael P. Hogan; Miguel Borja; Pollyanna Fernandes Campos; Felipe G. Grazziotin; Darin R. Rokyta; et al. (Toxicon, 2023)

Transcriptomic Profiling Reveals Discrete Poststroke Dementia Neuronal and Gliovascular Signatures - Rachel Waller; Yoshiki Hase; Julie E. Simpson; Paul R. Heath; Matthew Wyles; Rajesh N. Kalaria; Stephen B. Wharton (Translational Stroke Research, 2023)
Poststroke dementia (PSD) is associated with pathology in frontal brain regions, in particular dorsolateral prefrontal cortex (DLPFC) neurons and white matter, remote from the infarct. We hypothesised that PSD results from progressive DLPFC neuronal damage, associated with frontal white matter gliovascular unit (GVU) alterations. We investigated the transcriptomic profile of the neurons and white matter GVU cells previously implicated in pathology. Laser-capture microdissected neurons, astrocytes and endothelial cells were obtained from the Cognitive Function After Stroke cohort of control, PSD and poststroke non-dementia (PSND) human subjects. Gene expression was assessed using microarrays and pathway analysis to compare changes in PSD with controls and PSND. Neuronal findings were validated using NanoString technology and compared with those in the bilateral common carotid artery stenosis (BCAS) mouse model. Comparing changes in PSD compared to controls with changes in PSND compared to controls identified transcriptomic changes associated specifically with dementia. DLPFC neurons showed defects in energy production (tricarboxylic acid (TCA) cycle, adenosine triphosphate (ATP) binding and mitochondria), signalling and communication (MAPK signalling, Toll-like receptor signalling, endocytosis). Similar changes were identified in neurons isolated from BCAS mice. Neuronal findings accompanied by altered astrocyte communication and endothelium immune changes in the frontal white matter, suggesting GVU dysfunction. We propose a pathogenic model in PSD whereby neuronal changes are associated with frontal white matter GVU dysfunction leading to astrocyte failure in supporting neuronal circuits resulting in delayed cognitive decline associated with PSD. Therefore, targeting these processes could potentially ameliorate the dementia seen in PSD.

Hydrologic responses of single land use urban and forested watersheds and their implications to improving urban drainage design - Ian M. Simpson; Ryan J. Winston; R. Andrew Tirpak; Jay D. Dorsey; James H. Stagge; Jon M. Hathaway (Journal of Hydrology, 2023)

Gene flow connects key leopard (Panthera pardus) populations despite habitat fragmentation and persecution - Declan R. Morris; Todd J. McWhorter; Wayne S. J. Boardman; Greg Simpson; Jeanette Wentzel; Jannie Coetzee; Ferreira Du Plessis; Yoshan Moodley (Biodiversity and Conservation, 2023)

Effects of interactions between anthropogenic stressors and recurring perturbations on ecosystem resilience and collapse - David A. Keith; Doug H. Benson; Ian R. C. Baird; Laura Watts; Christopher C. Simpson; Martin Krogh; Sarsha Gorissen; Jose R. Ferrer‐Paris; Tanya J. Mason (Conservation Biology, 2023)
Insights into declines in ecosystem resilience and their causes and effects can inform preemptive action to avoid ecosystem collapse and loss of biodiversity, ecosystem services, and human well‐being. Empirical studies of ecosystem collapse are rare and hampered by ecosystem complexity, nonlinear and lagged responses, and interactions across scales. We investigated how an anthropogenic stressor could diminish ecosystem resilience to a recurring perturbation by altering a critical ecosystem driver. We studied groundwater‐dependent, peat‐accumulating, fire‐prone wetlands known as upland swamps in southeastern Australia. We hypothesized that underground mining (stressor) reduces resilience of these wetlands to landscape fires (perturbation) by diminishing groundwater, a key ecosystem driver. We monitored soil moisture as an indicator of ecosystem resilience during and after underground mining. After landscape fire, we compared responses of multiple state variables representing ecosystem structure, composition, and function in swamps within the mining footprint with unmined reference swamps. Soil moisture declined without recovery in swamps with mine subsidence (i.e., undermined), but was maintained in reference swamps over 8 years (effect size 1.8). Relative to burned reference swamps, burned undermined swamps showed greater loss of peat via substrate combustion; reduced cover, height, and biomass of regenerating vegetation; reduced postfire plant species richness and abundance; altered plant species composition; increased mortality rates of woody plants; reduced postfire seedling recruitment; and extirpation of a hydrophilic animal. Undermined swamps therefore showed strong symptoms of postfire ecosystem collapse, whereas reference swamps regenerated vigorously. We found that an anthropogenic stressor diminished the resilience of an ecosystem to recurring perturbations, predisposing it to collapse. Avoidance of ecosystem collapse hinges on early diagnosis of mechanisms and preventative risk reduction. It may be possible to delay or ameliorate symptoms of collapse or to restore resilience, but the latter appears unlikely in our study system due to fundamental alteration of a critical ecosystem driver. Efectos de las interacciones entre los estresantes antropogénicos y las perturbaciones recurrentes sobre la resiliencia y el colapso de los ecosistemas

Ecological and economic implications of alternative metrics in biodiversity offset markets - Katherine Hannah Simpson; Frans P. de Vries; Martin Dallimer; Paul R. Armsworth; Nick Hanley (Conservation Biology, 2022)
Policy tools are needed that allow reconciliation of human development pressures with conservation priorities. Biodiversity offsetting can be used to compensate for ecological losses caused by development activities. Landowners can choose to undertake conservation actions, including habitat restoration, to generate biodiversity offsets. Consideration of the incentives facing landowners as potential biodiversity offset providers and developers as potential buyers of credits is critical when considering the ecological and economic landscape‐scale outcomes of alternative offset metrics. There is an expectation that landowners will always seek to conserve the least profitable land parcels, and, in turn, this determines the spatial location of biodiversity offset credits. We developed an ecological‐economic model to compare the ecological and economic outcomes of offsetting for a habitat‐based metric and a species‐based metric. We were interested in whether these metrics would adequately capture the indirect benefits of offsetting on species not considered under a no‐net‐loss policy. We simulated a biodiversity offset market for a case study landscape, linking species distribution modeling and an economic model of landowner choice based on economic returns of the alternative land management options (restore, develop, or maintain existing land use). Neither the habitat nor species metric adequately captured the indirect benefits of offsetting on related habitats or species. The underlying species distributions, layered with the agricultural and development rental values of parcels, resulted in very different landscape outcomes depending on the metric chosen. If policy makers are aiming for the metric to act as an indicator to mitigate impacts on a range of closely related habitats and species, then a simple no‐net‐loss target is not adequate. Furthermore, to achieve the most ecologically beneficial design of offsets policy, an understanding of the economic decision‐making processes of the landowners is needed.

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Population density estimate of leopards (Panthera pardus) in north-western Mpumalanga, South Africa, determined using spatially explicit capture–recapture methods - Declan R. Morris; Wayne S. J. Boardman; Lourens H. Swanepoel; Greg Simpson; Jannie Coetzee; Gerrie J. Camacho; Todd J. McWhorter (Mammalian Biology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Organic anions facilitate the mobilization of soil organic phosphorus and its subsequent lability to phosphatases - Alan E. Richardson; Timothy S. George; Maarten Hens; Emmanuel Delhaize; Peter R. Ryan; Richard J. Simpson; Peter J. Hocking (Plant and Soil, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Abrupt changes in the physical and biological structure of endorheic upland lakes due to 8‐m lake‐level variation during the 20 th century - Judith A. Bjorndahl; Cale A.C. Gushulak; Stefano Mezzini; Gavin L. Simpson; Heather A. Haig; Peter R. Leavitt; Kerri Finlay (Limnology and Oceanography, 2022)
Climate‐induced variation in lake level can affect physicochemical properties of endorheic lakes, but its consequences for phototrophic production and regime shifts are not well understood. Here, we quantified changes in the abundance and community composition of phototrophs in Kenosee and White Bear lakes, two endorheic basins in the parkland Moose Mountain uplands of southeastern Saskatchewan, Canada, which have experienced > 8 m declines in water level since ~ 1900. We hypothesized that lower water levels and warmer temperatures should manifest as increased abundance of phytoplankton, particularly cyanobacteria, and possibly trigger a regime shift to turbid conditions due to evaporative concentration of nutrients and solutes. High‐resolution analysis of sedimentary pigments revealed an increase in total phototrophic abundance (as β‐carotene) concurrent with lake‐level decline beginning ~ 1930, but demonstrated little directional change in cyanobacteria. Instead, significant increases in obligately anaerobic purple sulfur bacteria (as okenone) occurred in both lakes during ~ 1930–1950, coeval with alterations to light environments and declines in lake level. The presence of okenone suggests that climate‐induced increases in solute concentrations may have favored the formation of novel bacterial habitats where photic and anoxic zones overlapped. Generalized additive models showed that establishment of this unique habitat was likely preceded by increased temporal variance of sulfur bacteria, but not phytoplankton or cyanobacteria, suggesting that this abrupt change to physical lake structure was unique to deep‐water environments. Such climate‐induced shifts may become more frequent in the region due to hydrological stress on lake levels due to warming temperatures across the Northern Great Plains.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Anthropogenic Mixing in Seasonally Stratified Shelf Seas by Offshore Wind Farm Infrastructure - Robert M. Dorrell; Charlie J. Lloyd; Ben J. Lincoln; Tom P. Rippeth; John R. Taylor; Colm-cille P. Caulfield; Jonathan Sharples; Jeff A. Polton; Brian D. Scannell; Deborah M. Greaves; Rob A. Hall; John H. Simpson (Frontiers in Marine Science, 2022)
The offshore wind energy sector has rapidly expanded over the past two decades, providing a renewable energy solution for coastal nations. Sector development has been led in Europe, but is growing globally. Most developments to date have been in well-mixed, i.e., unstratified, shallow-waters near to shore. Sector growth is, for the first time, pushing developments to deep water, into a brand new environment: seasonally stratified shelf seas. Seasonally stratified shelf seas, where water density varies with depth, have a disproportionately key role in primary production, marine ecosystem and biogeochemical cycling. Infrastructure will directly mix stratified shelf seas. The magnitude of this mixing, additional to natural background processes, has yet to be fully quantified. If large enough it may erode shelf sea stratification. Therefore, offshore wind growth may destabilize and fundamentally change shelf sea systems. However, enhanced mixing may also positively impact some marine ecosystems. This paper sets the scene for sector development into this new environment, reviews the potential physical and environmental benefits and impacts of large scale industrialization of seasonally stratified shelf seas and identifies areas where research is required to best utilize, manage, and mitigate environmental change.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Bird rookery nutrient over-enrichment as a potential accelerant of mangrove cay decline in Belize - L. T. Simpson; S. W. J. Canty; J. R. Cissell; M. K. Steinberg; J. A. Cherry; I. C. Feller (Oecologia, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Unexpected shift from phytoplankton to periphyton in eutrophic streams due to wastewater influx - Nathanael T. Bergbusch; Nicole M. Hayes; Gavin L. Simpson; Peter R. Leavitt (Limnology and Oceanography, 2021)
Pollution with nitrogen (N) and phosphorous (P) impairs streams by favoring suspended algae and cyanobacteria over diatom‐rich periphyton. Recently, wastewater treatment plants have been upgraded to biological nutrient removal to eliminate both P and N (mainly NH 4 + ), although little is known of the effects of this effluent on flowing waters. Here, we used high performance liquid chromatography to quantify how the abundance and composition of phytoplankton and periphyton varied in response to both influx of effluent produced by biological nutrient removal and physico‐chemical conditions in small, turbid, P‐rich streams of the northern Great Plains. At the catchment scale, analysis with generalized additive models (GAMs) explained 40.5–62.6% of deviance in total phototroph abundance (as Chl a ) and 72.5–82.5% of deviance in community composition (as biomarker carotenoids) in both planktonic and benthic habitats when date‐ and site‐specific physico‐chemical parameters were used as predictors. In contrast, GAMs using wastewater input (as aqueous δ 15 N) as a predictor explained up to 50% of deviance in Chl a , and ~60% of deviance in community composition, in both suspended (51.6% of Chl a , 67.1% of composition) and attached communities (21.5% of Chl a , 58.8% of composition). Phytoplankton was replaced by periphyton within a 60‐km wastewater‐impacted reach due to dilution of streams by transparent effluent and addition of urban NO 3 − , although predominance of phytoplankton was re‐established after confluence with higher‐order streams. Overall, influx of effluent shifted turbid, phytoplankton‐rich streams to clear ecosystems with abundant epilithon by improving water transparency and providing NO 3 − to favor benthic diatoms and chlorophytes.

The effects of normoxic endurance exercise on erythropoietin (EPO) production and the impact of selective β1 and non-selective β1 + β2 adrenergic receptor blockade - Rod J. Azadan; Nadia H. Agha; Hawley E. Kunz; Forrest L. Baker; Preteesh L. Mylabathula; Tracy A. Ledoux; Daniel P. O’Connor; Charles R. Pedlar; Richard J. Simpson (European Journal of Applied Physiology, 2021)

The Human Element of Restoration Success: Manager Characteristics Affect Vegetation Recovery Following Invasive Tamarix Control - Anna A. Sher; Lisa Clark; Annie L. Henry; Alexander R. B. Goetz; Eduardo González; Anit Tyagi; Isabelle Simpson; Bérenger Bourgeois (Wetlands, 2020)

Crop rotations differ in soil carbon stabilization efficiency, but the response to quality of structural plant inputs is ambiguous - Alison E. King; Katelyn A. Congreves; Bill Deen; Kari E. Dunfield; Myrna J. Simpson; R. Paul Voroney; Claudia Wagner-Riddle (Plant and Soil, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

A Citizen Science State of the World’s Wetlands Survey - R. J. McInnes; N. C. Davidson; C. P. Rostron; M. Simpson; C. M. Finlayson (Wetlands, 2020)

Genomic sequencing highlights the diverse molecular causes of Perrault syndrome: a peroxisomal disorder (PEX6), metabolic disorders (CLPP, GGPS1), and mtDNA maintenance/translation disorders (LARS2, TFAM) - Elena J. Tucker; Rocio Rius; Sylvie Jaillard; Katrina Bell; Phillipa J. Lamont; André Travessa; Juliette Dupont; Lurdes Sampaio; Jérôme Dulon; Sandrine Vuillaumier-Barrot; Sandra Whalen; Arnaud Isapof; et al. (Human Genetics, 2020)

Bayesian Inverse Transient Analysis for Pipeline Condition Assessment: Parameter Estimation and Uncertainty Quantification - Chi Zhang; Martin F. Lambert; Jinzhe Gong; Aaron C. Zecchin; Angus R. Simpson; Mark L. Stephens (Water Resources Management, 2020)

Soil phosphorus pools with addition of fertiliser phosphorus in a long-term grazing experiment - Timothy I. McLaren; Ronald J. Smernik; Michael J. McLaughlin; Therese M. McBeath; Malcolm R. McCaskill; Fiona A. Robertson; Richard J. Simpson (Nutrient Cycling in Agroecosystems, 2020)

MicroRNA-34a Acutely Regulates Synaptic Efficacy in the Adult Dentate Gyrus In Vivo - Birgitte Berentsen; Sudarshan Patil; Kine Rønnestad; Kevin M. Goff; Maciej Pajak; T. Ian Simpson; Karin Wibrand; Clive R. Bramham (Molecular Neurobiology, 2020)

The impact of acute and chronic exercise on Nrf2 expression in relation to markers of mitochondrial biogenesis in human skeletal muscle - Hashim Islam; Jacob T. Bonafiglia; Patrick C. Turnbull; Craig A. Simpson; Christopher G. R. Perry; Brendon J. Gurd (European Journal of Applied Physiology, 2020)

Blue Carbon: an Additional Driver for Restoring and Preserving Ecological Services of Coastal Wetlands in Tampa Bay (Florida, USA) - Lindsey Sheehan; Edward T. Sherwood; Ryan P. Moyer; Kara R. Radabaugh; Stefanie Simpson (Wetlands, 2019)

Epichloe novae‐zelandiae , a new endophyte from the endemic New Zealand grass Poa matthewsii - Adrian Leuchtmann; Carolyn A. Young; Alan V. Stewart; Wayne R. Simpson; David E. Hume; Barry Scott (New Zealand Journal of Botany, 2019)
Epichloe endophytes (Clavicipitaceae) infect pooid grass genera worldwide but predominantly in the Northern Hemisphere, but appear to be rare in native grasses of the Southern Hemisphere. Because of benefits that hosts may receive from the symbiosis, Epichloe endophytes have been extensively studied and are considered important components of sustainable agriculture. There are only a few studies available on the incidence of endophyte infection in grasses of the Southern Hemisphere and most grass species have never been examined. Here we report on a survey of native grasses of New Zealand including 25 endemic or indigenous species. We sampled up to 10 plants per species at different sites from both the North and South Island of New Zealand and examined tissues microscopically for endophyte infection. Overall, only two species were found to be infected, Poa matthewsii (Matthew's bluegrass) and Dichelachne micrantha (short‐hair plume grass). Based on analyses of tefA and tubB genes, both endophytes were found to be interspecific hybrids. The endophyte of the new host D. micrantha was previously described as Epichloe australiensis , while the endophyte of P. matthewsii is a new species named here E. novae‐zelandiae . The new species is a hybrid derived from E. amarillans , E. bromicola and E. typhina subsp. poae. Alkaloid analyses in planta suggested that E. novae‐zelandiae can produce small amounts of peramine, early pathway indole‐diterpenes and ergot alkaloids, but no lolines or lolitrems. Target specific primers suggested the presence of genes for ergot alkaloids and peramine, but genes of only early pathway steps for the other alkaloids. Furthermore, genes for both mating type idiomorphs ( MTA and MTB ) were present, a single copy of MTA and two copies of MTB . Endophytes of native grasses may provide a genetic resource that could be exploited for developing pasture grass cultivars with improved performance.

Perspectives on in situ Sensors for Ocean Acidification Research - Akash R. Sastri; James R. Christian; Eric P. Achterberg; Dariia Atamanchuk; Justin J. H. Buck; Philip Bresnahan; Patrick J. Duke; Wiley Evans; Stephen F. Gonski; Bruce Johnson; S. Kim Juniper; Steve Mihaly; et al. (Frontiers in Marine Science, 2019)

Molecular Diagnosis of Emmonsia-Like Fungi Occurring in Wild Animals - P. Danesi; C. Falcaro; K. Dukik; Y. Jiang; A. P. Rizzoli; R. Allavena; V. Simpson; S. Ravagnan; C. Zanardello; G. Capelli; G. S. de Hoog (Mycopathologia, 2019)

Sensor Placement Strategy for Pipeline Condition Assessment Using Inverse Transient Analysis - Chi Zhang; Jinzhe Gong; Martin F. Lambert; Angus R. Simpson; Aaron C. Zecchin (Water Resources Management, 2019)

Inbreeding depression causes reduced fecundity in Golden Retrievers - Erin T. Chu; Missy J. Simpson; Kelly Diehl; Rodney L. Page; Aaron J. Sams; Adam R. Boyko (Mammalian Genome, 2019)

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

Melt segregation and the architecture of magmatic reservoirs: insights from the Muroto sill (Japan) - David Floess; Luca Caricchi; Guy Simpson; Simon R. Wallis (Contributions to Mineralogy and Petrology, 2019)

Seasonality of pCO 2 in a hard‐water lake of the northern Great Plains: The legacy effects of climate and limnological conditions over 36 years - Kerri Finlay; Richard J. Vogt; Gavin L. Simpson; Peter R. Leavitt (Limnology and Oceanography, 2019)
Biogeochemical processes are active year‐round in ice‐covered lakes, such that processes in one season can affect limnological conditions in subsequent seasons. However, the extent and nature of these legacy effects are poorly understood, particularly for the CO 2 content of lakes and when considering gas exchange with the atmosphere. Here, we used a unique 36‐yr dataset of weekly limnological measurements of Buffalo Pound Lake in the northern Great Plains to assess seasonal changes in CO 2 concentration and flux and determine how dependent lake pCO 2 is on limnological conditions of previous seasons. We found that the lake was a net source of CO 2 to the atmosphere (mean 18.5 ± 7.4 mol CO 2 m −2 yr −1 ), with spring potentially accounting for the majority (~ 64% ± 20%) of CO 2 efflux, assuming ice in spring was permeable to gas exchange (32.9% ± 19.8% if not). Analysis with generalized additive models (GAMs) demonstrated that current and antecedent seasonal conditions combined to explain 72.6% of deviance in spring pCO 2 , but that the strength of model predictions and the importance of antecedent conditions diminished in GAMs of summer (43.6%) and fall (23.3%) CO 2 levels. This research suggests that pCO 2 is regulated by a combination of coeval and historical environmental conditions and shows that quantification of seasonal and annual fluxes requires a mechanistic understanding of the legacy effects of preceding time intervals.

Differential stimulation and suppression of phytoplankton growth by ammonium enrichment in eutrophic hardwater lakes over 16 years - Vanessa J. Swarbrick; Gavin L. Simpson; Patricia M. Glibert; Peter R. Leavitt (Limnology and Oceanography, 2019)
Previous research suggests that fertilization of surface waters with chemically reduced nitrogen (N), including ammonium (NH 4 + ), may either enhance or suppress phytoplankton growth. To identify the factors influencing the net effect of NH 4 + , we fertilized natural phytoplankton assemblages from two eutrophic hardwater lakes with growth‐saturating concentrations of NH 4 Cl in 241 incubation experiments conducted biweekly May–August during 1996–2011. Phytoplankton biomass (as chlorophyll a ) was significantly ( p 4 + increased with abundance of diatoms, cryptophytes, and unicellular cyanobacteria, particularly when water temperatures and soluble reactive phosphorus (SRP) concentrations were low. In contrast, phytoplankton was often stimulated by NH 4 + when chlorophytes and non‐N 2 ‐fixing cyanobacteria were abundant, and temperatures and SRP concentrations were high. Progressive intensification of NH 4 + effects over 16 yr reflects changes in both spring (cooler water, increased diatoms and cryptophytes) and summer lake conditions (more chlorophytes, earlier cyanobacteria blooms), suggesting that the seasonal effects of NH 4 + will vary with future climate change and modes of N enrichment.

Structural and sampling uncertainty in observed UK daily precipitation extremes derived from an intercomparison of gridded data sets - Ian R. Simpson; Mark P. McCarthy (International Journal of Climatology, 2019)
This paper compares multiple gridded data sets of daily UK precipitation to evaluate structural uncertainty in our reconstructions of historical rainfall. The data sets compared reflect two different sampling strategies and three different grid interpolation methods. In order to separate the influence of sampling and interpolation uncertainties, one of the data sets (produced by the Met Office) has been recreated using the sampling strategy of stations used in the European (E‐OBS) data set. The results confirm and build upon previous studies showing that relying on a relatively sparse but homogeneous network of stations limits the ability of the resulting data set to reliably estimate extreme rainfall at the daily timescale. It is shown that gridding methods that additionally make use of reference climatological data can avoid systematic bias in both the average and extreme events even when using a relatively sparse network of observations. This is an encouraging result in terms of our potential to reliably extend such data sets further back in time where the availability of digitized data is substantially lower than the more modern era.

Physical and chemical impacts of a major storm on a temperate lake: a taste of things to come? - R. Iestyn Woolway; John H. Simpson; David Spiby; Heidrun Feuchtmayr; Ben Powell; Stephen C. Maberly (Climatic Change, 2018)

Changes in nutritional values induced by butachlor in juvenile diploid and triploid Clarias gariepinus - A. Karami; S. Karbalaei; M. Ebrahimi; A. Ismail; M. F. Jahromi; S. L. Simpson; P. Eghtesadi Araghi; R. P. Lim; J. B. Liang (International Journal of Environmental Science and Technology, 2018)

Typification of Piper species (Piperaceae) in Southeast Asia, especially Thailand - C. Suwanphakdee; D. A. Simpson; T. R. Hodkinson; P. Chantaranothai (Kew Bulletin, 2018)

Environmental exposure and parental collection does not affect detection or semi-quantitative load assessment of bacteria in nasal swab specimens from children - Nada Townsi; Shannon J. Simpson; Chisha T. Sikazwe; Glenys R. Chidlow; Graham L. Hall; J. Jane Pillow; Andrew C. Wilson; David W. Smith; Ingrid A. Laing (Infectious Diseases, 2018)

Influence of fascicle length on twitch potentiation of the medial gastrocnemius across three ankle angles - Samantha L. Kuzyk; Rowan R. Smart; Carey L. Simpson; Andrey Fedorov; Jennifer M. Jakobi (European Journal of Applied Physiology, 2018)

Differences in nutrient foraging among Trifolium subterraneum cultivars deliver improved P-acquisition efficiency - Rebecca E. Haling; Lawrie K. Brown; Adam Stefanski; Daniel R. Kidd; Megan H. Ryan; Graeme A. Sandral; Timothy S. George; Hans Lambers; Richard J. Simpson (Plant and Soil, 2018)

The carboxylate composition of rhizosheath and root exudates from twelve species of grassland and crop legumes with special reference to the occurrence of citramalate - Daniel R. Kidd; Megan H. Ryan; Dorothee Hahne; Rebecca E. Haling; Hans Lambers; Graeme A. Sandral; Richard J. Simpson; Gregory R. Cawthray (Plant and Soil, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Historical Processes and Contemporary Anthropogenic Activities Influence Genetic Population Dynamics of Nassau Grouper (Epinephelus striatus) within The Bahamas - Krista D. Sherman; R. Andrew King; Craig P. Dahlgren; Stephen D. Simpson; Jamie R. Stevens; Charles R. Tyler (Frontiers in Marine Science, 2017)

Regional climate changes drive increased scaled-chrysophyte abundance in lakes downwind of Athabasca Oil Sands nitrogen emissions - Graham R. Mushet; Kathleen R. Laird; Biplob Das; Brittany Hesjedal; Peter R. Leavitt; Kenneth A. Scott; Gavin L. Simpson; Björn Wissel; Jared D. Wolfe; Brian F. Cumming (Journal of Paleolimnology, 2017)

Energy input and dissipation in a temperate lake during the spring transition - R. Iestyn Woolway; John H. Simpson (Ocean Dynamics, 2017)

Time Dependent Behaviour of Trabecular Bone at Multiple Load Levels - Shuqiao Xie; Krishnagoud Manda; Robert J. Wallace; Francesc Levrero-Florencio; A. Hamish R. W. Simpson; Pankaj Pankaj (Annals of Biomedical Engineering, 2017)

Advanced Backcross Quantitative Trait Loci (QTL) Analysis of Oil Concentration and Oil Quality Traits in Peanut (Arachis hypogaea L.) - Jeffrey N. Wilson; Ratan Chopra; Michael R. Baring; Michael Gomez Selvaraj; Charles E. Simpson; Jennifer Chagoya; Mark D. Burow (Tropical Plant Biology, 2017)

Root morphology acclimation to phosphorus supply by six cultivars of Trifolium subterraneum L - Robert P. Jeffery; Richard J. Simpson; Hans Lambers; Daniel R. Kidd; Megan H. Ryan (Plant and Soil, 2017)

Characterization of carbon monoxide, methane and nonmethane hydrocarbons in emerging cities of Saudi Arabia and Pakistan and in Singapore - Barbara Barletta; Isobel J. Simpson; Nicola J. Blake; Simone Meinardi; Louisa K. Emmons; Omar S. Aburizaiza; Azhar Siddique; Jahan Zeb; Liya E. Yu; Haider A. Khwaja; Muhammad A. Farrukh; Donald R. Blake (Journal of Atmospheric Chemistry, 2017)

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

Duration of fascicle shortening is affected by muscle architecture and sex - C. L. Simpson; S. Arefin; R. R. Smart; B. Harwood; Jennifer M. Jakobi (European Journal of Applied Physiology, 2016)

Growth and root dry matter allocation by pasture legumes and a grass with contrasting external critical phosphorus requirements - Rebecca E. Haling; Zongjian Yang; Natalie Shadwell; Richard A. Culvenor; Adam Stefanski; Megan H. Ryan; Graeme A. Sandral; Daniel R. Kidd; Hans Lambers; Richard J. Simpson (Plant and Soil, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

Rhizosphere carboxylates and morphological root traits in pasture legumes and grasses - Daniel R. Kidd; Megan H. Ryan; Rebecca E. Haling; Hans Lambers; Graeme A. Sandral; Zongjian Yang; Richard A. Culvenor; Gregory R. Cawthray; Adam Stefanski; Richard J. Simpson (Plant and Soil, 2016)

The effects of pharmacological modulation of the serotonin 2C receptor on goal-directed behavior in mice - Matthew R. Bailey; Cait Williamson; Chris Mezias; Vanessa Winiger; Rae Silver; Peter D. Balsam; Eleanor H. Simpson (Psychopharmacology, 2016)

A model-based approach for imputing censored data in source apportionment studies - Jenna R. Krall; Charles H. Simpson; Roger D. Peng (Environmental and Ecological Statistics, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Chemical characterization and in vitro toxicity of diesel exhaust particulate matter generated under varying conditions - Julie Richman Fox; David P. Cox; Bertram E. Drury; Timothy R. Gould; Terrance J. Kavanagh; Michael H. Paulsen; Lianne Sheppard; Christopher D. Simpson; James A. Stewart; Timothy V. Larson; Joel D. Kaufman (Air Quality, Atmosphere & Health, 2015)

Marine extinction risk shaped by trait–environment interactions over 500 million years - Emily A. Orzechowski; Rowan Lockwood; Jarrett E. K. Byrnes; Sean C. Anderson; Seth Finnegan; Zoe V. Finkel; Paul G. Harnik; David R. Lindberg; Lee Hsiang Liow; Heike K. Lotze; Craig R. McClain; Jenny L. McGuire; et al. (Global Change Biology, 2015)
Perhaps the most pressing issue in predicting biotic responses to present and future global change is understanding how environmental factors shape the relationship between ecological traits and extinction risk. The fossil record provides millions of years of insight into how extinction selectivity (i.e., differential extinction risk) is shaped by interactions between ecological traits and environmental conditions. Numerous paleontological studies have examined trait‐based extinction selectivity; however, the extent to which these patterns are shaped by environmental conditions is poorly understood due to a lack of quantitative synthesis across studies. We conducted a meta‐analysis of published studies on fossil marine bivalves and gastropods that span 458 million years to uncover how global environmental and geochemical changes covary with trait‐based extinction selectivity. We focused on geographic range size and life habit (i.e., infaunal vs. epifaunal), two of the most important and commonly examined predictors of extinction selectivity. We used geochemical proxies related to global climate, as well as indicators of ocean acidification, to infer average global environmental conditions. Life‐habit selectivity is weakly dependent on environmental conditions, with infaunal species relatively buffered from extinction during warmer climate states. In contrast, the odds of taxa with broad geographic ranges surviving an extinction (>2500 km for genera, >500 km for species) are on average three times greater than narrow‐ranging taxa (estimate of odds ratio: 2.8, 95% confidence interval = 2.3–3.5), regardless of the prevailing global environmental conditions. The environmental independence of geographic range size extinction selectivity emphasizes the critical role of geographic range size in setting conservation priorities.

Next-generation transcriptome sequencing, SNP discovery and validation in four market classes of peanut, Arachis hypogaea L. - Ratan Chopra; Gloria Burow; Andrew Farmer; Joann Mudge; Charles E. Simpson; Thea A. Wilkins; Michael R. Baring; Naveen Puppala; Kelly D. Chamberlin; Mark D. Burow (Molecular Genetics and Genomics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

Investigation of insecticide leaching from potted nursery stock and aquatic health benefits of bioretention cells receiving nursery runoff - Grant M. Graves; Jason R. Vogel; Jason B. Belden; Eric J. Rebek; Adam M. Simpson (Environmental Science and Pollution Research, 2014)

Cyperus beentjei, a new species of Cyperaceae from Tropical East Africa delimited through morphometric analysis - Lucinda R. Gardner; Odile Weber; David A. Simpson (Kew Bulletin, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Analysis of UK precipitation extremes derived from Met Office gridded data - I. R. Simpson; P. D. Jones (International Journal of Climatology, 2014)
In Simpson and Jones (2012) we introduced new, homogenized UK national and regional rainfall series derived from 5 km gridded daily and monthly precipitation data. The monthly series were extended back to 1766 for monthly England and Wales ( EW ) precipitation, to 1873 for monthly values for each of the five EW sub‐regions, and to 1931 for daily values in all regions. Using data from those series, this paper provides analysis of how mean precipitation totals and extremes have changed over the respective periods. The results showed statistically significant upward trends in mean and extreme winter, spring and autumn precipitation for some Scottish regions, but trends over England and Wales were mostly insignificant, though England and Wales had a significant increase in winter precipitation over 1766–2011. The trend in summer precipitation over 1931–2011 has been statistically insignificant, though with a significant long‐term downward trend for England and Wales over 1766–2011. Prior observations of a trend towards drier summers and wetter winters have been complicated by a recent succession of wet summers and dry winters. Many of the observed changes in seasonal precipitation totals are most likely associated with changes in the North Atlantic Oscillation.

Detecting Extinction Risk from Climate Change by IUCN Red List Criteria - DAVID A. KEITH; MICHAEL MAHONY; HARRY HINES; JANE ELITH; TRACEY J. REGAN; JOHN B. BAUMGARTNER; DAVID HUNTER; GEOFFREY W. HEARD; NICOLA J. MITCHELL; KIRSTEN M. PARRIS; TRENT PENMAN; BEN SCHEELE; et al. (Conservation Biology, 2014)
Anthropogenic climate change is a key threat to global biodiversity. To inform strategic actions aimed at conserving biodiversity as climate changes, conservation planners need early warning of the risks faced by different species. The IUCN Red List criteria for threatened species are widely acknowledged as useful risk assessment tools for informing conservation under constraints imposed by limited data. However, doubts have been expressed about the ability of the criteria to detect risks imposed by potentially slow‐acting threats such as climate change, particularly because criteria addressing rates of population decline are assessed over time scales as short as 10 years. We used spatially explicit stochastic population models and dynamic species distribution models projected to future climates to determine how long before extinction a species would become eligible for listing as threatened based on the IUCN Red List criteria. We focused on a short‐lived frog species (Assa darlingtoni) chosen specifically to represent potential weaknesses in the criteria to allow detailed consideration of the analytical issues and to develop an approach for wider application. The criteria were more sensitive to climate change than previously anticipated; lead times between initial listing in a threatened category and predicted extinction varied from 40 to 80 years, depending on data availability. We attributed this sensitivity primarily to the ensemble properties of the criteria that assess contrasting symptoms of extinction risk. Nevertheless, we recommend the robustness of the criteria warrants further investigation across species with contrasting life histories and patterns of decline. The adequacy of these lead times for early warning depends on practicalities of environmental policy and management, bureaucratic or political inertia, and the anticipated species response times to management actions. Detección del Riesgo de Extinción a partir del Cambio Climático por medio del Criterio de la Lista Roja de la UICNKeith et al.

Prevalence of polypharmacy in a Scottish primary care population - R. A. Payne; A. J. Avery; M. Duerden; C. L. Saunders; C. R. Simpson; G. A. Abel (European Journal of Clinical Pharmacology, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Estimates of twenty-first century sea-level changes for Norway - Matthew J. R. Simpson; Kristian Breili; Halfdan P. Kierulf (Climate Dynamics, 2014)

“The Ekman Drain”: a conduit to the deep ocean for shelf material - John H. Simpson; Robin R. McCandliss (Ocean Dynamics, 2013)

Latent cytomegalovirus infection and innate immune function following a 75 km cycling time trial - Emily C. P. LaVoy; David C. Nieman; Dru A. Henson; R. Andrew Shanely; Amy M. Knab; Lynn Cialdella-Kam; Richard J. Simpson (European Journal of Applied Physiology, 2013)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Consistent proportional macronutrient intake selected by adult domestic cats (Felis catus) despite variations in macronutrient and moisture content of foods offered - Adrian K. Hewson-Hughes; Victoria L. Hewson-Hughes; Alison Colyer; Andrew T. Miller; Simon R. Hall; David Raubenheimer; Stephen J. Simpson (Journal of Comparative Physiology B, 2013)

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

Considerations for modeling burn probability across landscapes with steep environmental gradients: an example from the Columbia Mountains, Canada - Marc-André Parisien; Gregg R. Walker; John M. Little; Brian N. Simpson; Xianli Wang; Daniel D. B. Perrakis (Natural Hazards, 2013)

The Benefits of Spatially Targeted Water Level Management for Salinity Reduction in a Coastal Aquifer - I. P. Holman; K. R. Rushton; T. B. Simpson (Water Resources Management, 2013)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

Updated precipitation series for the UK derived from Met Office gridded data - I. R. Simpson; P. D. Jones (International Journal of Climatology, 2012)
This paper introduces new, homogenized UK national and regional rainfall series derived from 5‐km gridded daily and monthly precipitation data. These new series have the advantage that they are based on readings from a dense network of rain gauges rather than a maximum of seven per region. Series developed by alternative statistical methods are analysed and compared. Error estimates are derived for the series, based on linear regressive residuals. Using individual regressions for each calendar month, the monthly series are extended back to 1766 for monthly precipitation in England and Wales (EW), to 1873 for monthly values for each of the five EW sub‐regions, and to 1931 for daily values in all regions. A follow‐up paper will provide analysis of how mean precipitation totals and extremes have changed over the respective periods. Copyright © 2011 Royal Meteorological Society

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

The impact of 6-month training preparation for an Ironman triathlon on the proportions of naïve, memory and senescent T cells in resting blood - Cormac Cosgrove; Stuart D. R. Galloway; Craig Neal; Angus M. Hunter; Brian K. McFarlin; Guilllaume Spielmann; Richard J. Simpson (European Journal of Applied Physiology, 2012)

Above‐ and belowground responses of arctic tundra ecosystems to altered soil nutrients and mammalian herbivory - Laura Gough; John C. Moore; Gauis R. Shaver; Rodney T. Simpson; David R. Johnson (Ecology, 2012)
Theory and observation indicate that changes in the rate of primary production can alter the balance between the bottom‐up influences of plants and resources and the top‐down regulation of herbivores and predators on ecosystem structure and function. The Exploitation Ecosystem Hypothesis (EEH) posited that as aboveground net primary productivity (ANPP) increases, the additional biomass should support higher trophic levels. We developed an extension of EEH to include the impacts of increases in ANPP on belowground consumers in a similar manner as aboveground, but indirectly through changes in the allocation of photosynthate to roots. We tested our predictions for plants aboveground and for phytophagous nematodes and their predators belowground in two common arctic tundra plant communities subjected to 11 years of increased soil nutrient availability and/or exclusion of mammalian herbivores. The less productive dry heath (DH) community met the predictions of EEH aboveground, with the greatest ANPP and plant biomass in the fertilized plots protected from herbivory. A palatable grass increased in fertilized plots while dwarf evergreen shrubs and lichens declined. Belowground, phytophagous nematodes also responded as predicted, achieving greater biomass in the higher ANPP plots, whereas predator biomass tended to be lower in those same plots (although not significantly). In the higher productivity moist acidic tussock (MAT) community, aboveground responses were quite different. Herbivores stimulated ANPP and biomass in both ambient and enriched soil nutrient plots; maximum ANPP occurred in fertilized plots exposed to herbivory. Fertilized plots became dominated by dwarf birch (a deciduous shrub) and cloudberry (a perennial forb); under ambient conditions these two species coexist with sedges, evergreen dwarf shrubs, and Sphagnum mosses. Phytophagous nematodes did not respond significantly to changes in ANPP, although predator biomass was greatest in control plots. The contrasting results of these two arctic tundra plant communities suggest that the predictions of EEH may hold for very low ANPP communities, but that other factors, including competition and shifts in vegetation composition toward less palatable species, may confound predicted responses to changes in productivity in higher ANPP communities such as the MAT studied here.

A microsatellite linkage map for the cultivated strawberry (Fragaria × ananassa) suggests extensive regions of homozygosity in the genome that may have resulted from breeding and selection - D. J. Sargent; T. Passey; N. Šurbanovski; E. Lopez Girona; P. Kuchta; J. Davik; R. Harrison; A. Passey; A. B. Whitehouse; D. W. Simpson (Theoretical and Applied Genetics, 2012)

Transgenic Stra8-EYFP pigs: a model for developing male germ cell technologies - Jeffrey R. Sommer; Lauren R. Jackson; Sean G. Simpson; Edwin B. Collins; Jorge A. Piedrahita; Robert M. Petters (Transgenic Research, 2012)

A doxycycline-inducible, tissue-specific aromatase-expressing transgenic mouse - Jenny D. Y. Chow; John T. Price; Margaret M. Bills; Evan R. Simpson; Wah Chin Boon (Transgenic Research, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Plant and microbial strategies to improve the phosphorus efficiency of agriculture - Alan E. Richardson; Jonathan P. Lynch; Peter R. Ryan; Emmanuel Delhaize; F. Andrew Smith; Sally E. Smith; Paul R. Harvey; Megan H. Ryan; Erik J. Veneklaas; Hans Lambers; Astrid Oberson; Richard A. Culvenor; et al. (Plant and Soil, 2011)

Strategies and agronomic interventions to improve the phosphorus-use efficiency of farming systems - Richard J. Simpson; Astrid Oberson; Richard A. Culvenor; Megan H. Ryan; Erik J. Veneklaas; Hans Lambers; Jonathan P. Lynch; Peter R. Ryan; Emmanuel Delhaize; F. Andrew Smith; Sally E. Smith; Paul R. Harvey; et al. (Plant and Soil, 2011)

Differential expression of Phaseolus vulgaris genes induced during the interaction with Rhizoctonia solani - M. L. Guerrero-González; M. Rodríguez-Kessler; R. Rodríguez-Guerra; M. González-Chavira; J. Simpson; F. Sanchez; J. F. Jiménez-Bremont (Plant Cell Reports, 2011)

Volcanology and petrology of Mathews Tuya, northern British Columbia, Canada: glaciovolcanic constraints on interpretations of the 0.730 Ma Cordilleran paleoclimate - Benjamin R. Edwards; James K. Russell; Kirstie Simpson (Bulletin of Volcanology, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

Volcanic threat in developing countries of the Asia–Pacific region: probabilistic hazard assessment, population risks, and information gaps - Alanna Simpson; R. Wally Johnson; Phil Cummins (Natural Hazards, 2011)

An Integrated Approach to Gene Discovery and Marker Development in Atlantic Cod (Gadus morhua) - Sharen Bowman; Sophie Hubert; Brent Higgins; Cynthia Stone; Jennifer Kimball; Tudor Borza; Jillian Tarrant Bussey; Gary Simpson; Catherine Kozera; Bruce A. Curtis; Jennifer R. Hall; Tiago S. Hori; et al. (Marine Biotechnology, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Vegetative reproduction facilitates early expansion of Phyla canescens in a semi-arid floodplain - J. N. Price; M. J. Macdonald; C. L. Gross; R. D. B. Whalley; I. H. Simpson (Biological Invasions, 2011)

Ice stream influence on West Greenland Ice Sheet dynamics during the Last Glacial Maximum - David H. Roberts; Antony J. Long; Bethan J. Davies; Matthew J. R. Simpson; Christoph Schnabel (Journal of Quaternary Science, 2010)
This paper investigates the processes governing bedrock bedform evolution in ice sheet and ice stream areas in central West Greenland, and explores the evidence for a cross‐shelf ice stream at the Last Glacial Maximum (LGM). To the east of Sisimiut the formation of streamlined bedforms with high elongation ratios and high bedform density has been controlled by geological structure and topography in slow‐flowing ice sheet areas. At the coast, the effects of regional flow convergence, caused by coastal fjord orientation, routed ice into the Sisimiut/Itilleq area where it formed an ice stream onset zone. This funnelled ice into an offshore trough (Holsteinsborg Dyb), resulting in a southwesterly regional ice flow direction and the formation of a topographically routed ice stream (Holsteinsborg Isbrae). To the south of this, striae and bedform evidence show that local valley glaciers initially flowed east to west across the coast, but were later redirected by the Itilleq Fjord ice which turned southwestward due to diffluent flow and deflection by Holsteinsborg Isbrae. Roches moutonnées in this area have low elongation ratios and high bedform density, but do not provide unequivocal support for ice streaming, as they are a product of both bedrock structure and changes in ice flow direction, rather than enhanced flow velocities. Cosmogenic surface exposure ages limit maximum ice sheet surface elevation to ca. 755–810 m above sea level in this region. Such ice thickness enabled Holsteinsborg Isbrae to reach the mid/outer continental shelf during the LGM, and to contribute to the formation of a trough mouth fan and the Outer Hellefisk moraines. Initial deglaciation across this region was driven by rising sea level and increasing air temperatures prior to the Bølling Interstadial at ca. 14.5 cal. ka BP. Between 12 and 10 cal. ka BP both increased air and ocean temperatures post the Younger Dryas, and peak sea‐level rise up to the marine limit, caused accelerated thinning and marginal retreat through calving, although dating evidence suggests ice streams remained along the inner shelf/coast boundary until at least ca. 10 cal. ka BP, their longevity maintained by increased ice thickness and ice discharge. Copyright © 2009 John Wiley & Sons, Ltd.

Paleolimnological evidence of the effects on lakes of energy and mass transfer from climate and humans - Peter R. Leavitt; S. C. Fritz; N. J. Anderson; P. A. Baker; T. Blenckner; L. Bunting; J. Catalan; D. J. Conley; W. O. Hobbs; E. Jeppesen; A. Korhola; S. McGowan; et al. (Limnology and Oceanography, 2009)
The premise of this article is that climate effects on lakes can be quantified most effectively by the integration of process‐oriented limnological studies with paleolimnological research, particularly when both disciplines operate within a common conceptual framework. To this end, the energy (E)‐mass ( m ) flux framework (E m flux) is developed and applied to selected retrospective studies to demonstrate that climate variability regulates lake structure and function over diverse temporal and spatial scales through four main pathways: rapid direct transfer of E to the lake surface by irradiance, heat, and wind; slow indirect effects of E via changes in terrestrial development and subsequent m subsidies to lakes; direct influx of m as precipitation, particles, and solutes from the atmosphere; and indirect influx of water, suspended particles, and dissolved substances from the catchment. Sedimentary analyses are used to illustrate the unique effects of each pathway on lakes but suggest that interactions among mechanisms are complex and depend on the landscape position of lakes, catchment characteristics, the range of temporal variation of individual pathways, ontogenetic changes in lake basins, and the selective effects of humans on m transfers. In particular, preliminary synthesis suggests that m influx can overwhelm the direct effects of E transfer to lakes, especially when anthropogenic activities alter m subsidies from catchments.

Adiaspiromycosis Due to Emmonsia crescens is Widespread in Native British Mammals - Andrew M. Borman; Vic R. Simpson; Michael D. Palmer; Christopher J. Linton; Elizabeth M. Johnson (Mycopathologia, 2009)

Toward increasing avian diversity: urban wildscapes programs - Amanda L. Aurora; Thomas R. Simpson; Michael F. Small; Kelly C. Bender (Urban Ecosystems, 2009)

Characterization of lipophilic drug binding to rat intestinal fatty acid binding protein - Tony Velkov; Maria L. R. Lim; James Horne; Jamie S. Simpson; Christopher J. H. Porter; Martin J. Scanlon (Molecular and Cellular Biochemistry, 2009)

Development of “universal” gene-specific markers from Malus spp. cDNA sequences, their mapping and use in synteny studies within Rosaceae - Daniel J. Sargent; Annalisa Marchese; David W. Simpson; Werner Howad; Felicidad Fernández-Fernández; Amparo Monfort; Pere Arús; Kate M. Evans; Kenneth R. Tobutt (Tree Genetics & Genomes, 2009)

Urban effects of Chennai on sea breeze induced convection and precipitation - Matthew Simpson; Sethu Raman; R. Suresh; U. C. Mohanty (Journal of Earth System Science, 2008)

Urban geochemistry: research strategies to assist risk assessment and remediation of brownfield sites in urban areas - I. Thornton; M. E. Farago; C. R. Thums; R. R. Parrish; R. A. R. McGill; N. Breward; N. J. Fortey; P. Simpson; S. D. Young; A. M. Tye; N. M. J. Crout; R. L. Hough; et al. (Environmental Geochemistry and Health, 2008)

Large-scale vulnerability assessments for natural hazards - David M. Simpson; R. Josh Human (Natural Hazards, 2008)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Nocturnal relocation of adult and juvenile coral reef fishes in response to reef noise - S. D. Simpson; A. Jeffs; J. C. Montgomery; R. D. McCauley; M. G. Meekan (Coral Reefs, 2008)

A role for mu opioid receptors in cocaine-induced activity, sensitization, and reward in the rat - Joseph A. Schroeder; Michele Hummel; Alpha D. Simpson; Rizwan Sheikh; Avery R. Soderman; Ellen M. Unterwald (Psychopharmacology, 2007)

Sea-breeze-initiated rainfall over the east coast of India during the Indian southwest monsoon - Matthew Simpson; Hari Warrior; Sethu Raman; P. A. Aswathanarayana; U. C. Mohanty; R. Suresh (Natural Hazards, 2007)

The Role for Sustainably Managed Forests in Climate Change Mitigation - Steven Ruddell; R. Sampson; Matt Smith; R. Giffen; James Cathcart; John Hagan; Daniel Sosland; John Godbee; John Heissenbuttel; Stephen Lovett; John Helms; William Price; et al. (Journal of Forestry, 2007)
The United States has not ratified the Kyoto Protocol, restricting the ability of forests from participating internationally as greenhouse gas (GHG) emission offset projects. As a result, a proliferation of different registry and program rules is occurring in the United States, providing an opportunity for the US forestry community to mitigate GHG emissions. This article addresses the Kyoto Protocol principles of additionality, permanence, and leakage, and challenges the way that these principles are being used to qualify forest offset projects as climate change mitigation measures. Policy initiatives are proposed for challenging policymakers and the forestry community to rethink sustainably managed forest offset project rules as the United States considers GHG emission reduction legislation.

Spring‐neap modulation of internal tide mixing and vertical nitrate fluxes at a shelf edge in summer - Jonathan Sharples; Jacqueline F. Tweddle; J. A. Mattias Green; Matthew R. Palmer; Young-Nam Kim; Anna E. Hickman; Patrick M. Holligan; C. Mark Moore; Tom P. Rippeth; John H. Simpson; Vladimir Krivtsov (Limnology and Oceanography, 2007)
Measurements of the intra‐tidal and spring‐neap variation in the vertical flux of nitrate into the base of the sub‐surface chlorophyll maximum (SCM) were made at the shelf edge of the Celtic Sea, a region with strong internal mixing driven by an internal tide. The neap tide daily mean nitrate flux was 1.3 (0.9‐1.8, 95% confidence interval) mmol m ‐2 d ‐1 . The spring tide flux was initially estimated as 3.5 (2.3‐5.2, 95% confidence interval) mmol m ‐2 d ‐1 . The higher spring tide nitrate flux was the result of turbulent dissipation occurring within the base of the SCM as compared to deeper dissipation during neap tides and was dominated by short events associated with the passage of internal solitons. Taking into account the likely under‐sampling of these short mixing events raised the spring tide nitrate flux estimate to about 9 mmol m ‐2 d ‐1 . The neap tide nitrate flux was sufficient to support substantial new production and a considerable fraction of the observed rates of carbon fixation. Spring tide fluxes were potentially in excess of the capacity of the phytoplankton community to uptake nitrate. This potential excess nitrate flux during spring tides may be utilized to support new production during the lower mixing associated with the transition toward neap tide. The shelf edge is shown to be a region with a significantly different phytoplankton community as compared to the adjacent Celtic Sea and northeast Atlantic Ocean, highlighting the role of gradients in physical processes leading to gradients in ecosystem structure.

The effects of AZD3582 [4-(nitroxy)butyl-(2S)-2-(6-methoxy-2-naphthyl) propanoate], and naproxen on key pathogenic steps in NSAID-enteropathy in the rat - M. Walley; G. Sigthorsson; C. Hotz-Behofsits; R. Simpson; I. Bjarnason (Inflammopharmacology, 2007)

The development and mapping of functional markers in Fragaria and their transferability and potential for mapping in other genera - D. J. Sargent; A. Rys; S. Nier; D. W. Simpson; K. R. Tobutt (Theoretical and Applied Genetics, 2006)

Morphology and response of roots of pasture species to phosphorus and nitrogen nutrition - J. O. Hill; R. J. Simpson; A. D. Moore; D. F. Chapman (Plant and Soil, 2006)

Effects of Sewage Sludge Disposal on Metal Content in the Sediment and Water of Mitchell Lake, San Antonio, Texas, USA - N. Simpson; D. Sarkar; R. Datta; S. Sharma (Bulletin of Environmental Contamination and Toxicology, 2006)

An enhanced microsatellite map of diploid Fragaria - D. J. Sargent; J. Clarke; D. W. Simpson; K. R. Tobutt; P. Arús; A. Monfort; S. Vilanova; B. Denoyes-Rothan; M. Rousseau; K. M. Folta; N. V. Bassil; N. H. Battey (Theoretical and Applied Genetics, 2006)

Ultraviolet Radiation at Places of Residence and the Development of Melanocytic Nevi in Children (Australia) - Dallas R. English; Elizabeth Milne; Julie A. Simpson (Cancer Causes & Control, 2006)

Municipal Forest Benefits and Costs in Five US Cities - Greg McPherson; James R. Simpson; Paula J. Peper; Scott E. Maco; Qingfu Xiao (Journal of Forestry, 2005)
Increasingly, city trees are viewed as a best management practice to control stormwater, an urban-heat–island mitigation measure for cleaner air, a CO2-reduction option to offset emissions, and an alternative to costly new electric power plants. Measuring benefits that accrue from the community forest is the first step to altering forest structure in ways that will enhance future benefits. This article describes the structure, function, and value of street and park tree populations in Fort Collins, Colorado; Cheyenne, Wyoming; Bismarck, North Dakota; Berkeley, California; and Glendale, Arizona. Although these cities spent $13–65 annually per tree, benefits ranged from $31 to $89 per tree. For every dollar invested in management, benefits returned annually ranged from $1.37 to $3.09. Strategies each city can take to increase net benefits are presented.

Measurements of Trace Gases in the Inflow of South China Sea Background Air and Outflow of Regional Pollution at Tai O, Southern China - T. Wang; H. Guo; D. R. Blake; Y. H. Kwok; I. J. Simpson; Y. S. Li (Journal of Atmospheric Chemistry, 2005)

Presence of carp, Cyprinus carpio , in the diet of the otter, Lutra lutra - J. R. BRITTON; J. S. SHEPHERD; S. TOMS; V. SIMPSON (Fisheries Management and Ecology, 2005)

Clinical validation of the NeuroScreen - Ronald J Ellis; Scott R Evans; David B Clifford; Lauren R Moo; Justin C McArthur; Ann C Collier; Constance Benson; Ron Bosch; David Simpson; Constantin T Yiannoutsos; Yijun Yang; Kevin Robertson; et al. (Journal of NeuroVirology, 2005)

Nectin-1/HveC Mediates herpes simplex virus type-1 entry into primary human sensory neurons and fibroblasts - Scott A Simpson; Michael D Manchak; Elizabeth J Hager; Claude Krummenacher; J Charles Whitbeck; Myron J Levin; Curt R Freed; Christine L Wilcox; Gary H Cohen; Roselyn J Eisenberg; Lewis I. Pizer (Journal of NeuroVirology, 2005)

A genetic linkage map of microsatellite, gene-specific and morphological markers in diploid Fragaria - D. J. Sargent; T. M. Davis; K. R. Tobutt; M. J. Wilkinson; N. H. Battey; D. W. Simpson (Theoretical and Applied Genetics, 2004)

Competitive interactions between Microdochium nivale var. majus , M. nivale var. nivale and Fusarium culmorum in planta and in vitro - Duncan R. Simpson; Martha A. Thomsett; Paul Nicholson (Environmental Microbiology, 2004)
Summary Microdochium nivale var. majus and var. nivale are economically important fungal pathogens of cereal seedlings, stem bases and ears, as is the toxigenic species Fusarium culmorum . Competition experiments on seedlings support an earlier report of differential host preference between the varieties of M. nivale on wheat and rye seedlings at 15°C, but showed that it does not extend across a broad range of temperatures. The studies showed that, although interaction is disadvantageous to the less virulent pathogen, it does not confer an advantage to the more virulent pathogen. In mixed inoculum experiments on wheat seedlings at 15°C and 20°C, F. culmorum suppressed the growth of both varieties of M. nivale . However, if M. nivale var. majus became established on the seedlings, it was able to co‐suppress colonization of wheat seedlings by F. culmorum . In contrast M. nivale var. nivale did not suppress F. culmorum significantly. The growth of M. nivale var. majus and F. culmorum was also co‐suppressed in liquid culture. Significantly, the accumulation of deoxynivalenol mycotoxin was also reduced in the mixed in vitro culture compared with axenic culture of F. culmorum . However, in vitro interaction studies on solidified media were of only limited use in predicting the outcome of competitions in planta .

COX-1, COX-2 and the topical effect in NSAID-induced enteropathy - C. M. Hotz-Behofsits; M. J. M. Walley; R. Simpson; I. T. Bjarnason (Inflammopharmacology, 2003)

Effects of administration of somatostatin‐14 and immunoneutralization of somatostatin on endocrine and growth responses in rainbow trout - B. C. Peterson; P. R. Simpson; K. D. Cain; R. H. Hardy; G. T. Schelling; T. L. Ott (Journal of Fish Biology, 2003)
Injection of somatostatin‐14 (SS‐14) at 5 ng g −1 body mass (BM) into rainbow trout Oncorhynchus mykiss decreased ( P r 2 = 0·54) levels of growth hormone (GH) (1·5 ± 0·9 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time when compared to controls. Somatostatin‐14 at 50 ng g −1 BM also decreased ( P = 0·064, q uadratic; r 2 = 0·30) levels of GH (3·6 ± 2·1 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time compared to controls. In a second study, passive immunization against SS‐14 (1 : 25 dose) increased ( P = 0·10, cubic, r 2 = 0·12) levels of GH (11·0 ± 4·8 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time. Passively immunizing against SS‐14 (1 : 50 dose) increased ( P r 2 = 0·10) levels of GH (8·2 ± 2·3 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time compared to controls. Overall, in the active immunization study there was no difference ( P > 0·10) in specific growth rate ( G ) or feed conversion ratio ( FCR ) between the three treatment groups during the 9 weeks of the study. Only four of the fish immunized against SS‐14, however, developed antibody titres against SS. Compared to controls, these fish exhibited a G of 0·89 ± 0·09 v. 0·56 ± 0·09% per 3 weeks and FCR of 0·80 ± 0·04 v. 1·20 ± 0·05 g g −1 . In SS‐14 immunized fish, levels of GH decreased ( P P G and FCR is dependent upon generation of antibody titres.

Characteristics of an ozone deposition module II: Sensitivity analysis - D. Simpson; J.-P. Tuovinen; L. Emberson; M. R. Ashmore (Water, Air, & Soil Pollution, 2003)

Plant collecting spread and densities: their potential impact on biogeographical studies in Thailand - J. A. N. Parnell; D. A. Simpson; J. Moat; D. W. Kirkup; P. Chantaranothai; P. C. Boyce; P. Bygrave; S. Dransfield; M. H. P. Jebb; J. Macklin; C. Meade; D. J. Middleton; et al. (Journal of Biogeography, 2003)
Aims To produce representative aggregate maps of plant collection locations in Thailand and discuss their impact on biogeographical studies in Thailand and the surrounding region. Location Thailand. Methods A representative data set comprising 6593 plant specimen records for Thailand has been assembled. The data set contains ± all known collections for fifteen representative plant families and further records for another 104. All records are localized to Changwat (province), 6441 to at least quarter degree square. Results Analysis shows that the spread of collecting activity in Thailand is markedly uneven; 20% of collections come from a single Changwat (Chiang Mai) and 53% of Changwat have fifty or fewer collections. The distribution of collections by Changwat and by quarter degree square is erratic with most squares and Changwat having few collections, both in proportionate and absolute terms. Some of the most densely forested Changwats and squares appear undercollected. Distribution maps for common, easily recognized tree species in the genus Syzygium show distributional gaps. Conclusions Thailand is defined as an undercollected country. Even within the few well‐collected quarter degree squares the spread of collecting is still poor; almost all collections being localized to one of three mountain ranges or their foothills. There are many gaps in collecting activity which make impossible a straightforward interpretation of biogeographical pattern. It is argued that targeted collecting activity is needed, that assembly of this type of data set is therefore essential and that our data set and its interpretation is a model for all countries in the region.

Movements and Habitat Use by the Endangered Australian Freshwater Mary River cod, Maccullochella peelii mariensis - Robert R. Simpson; Amos J. Mapleston (Environmental Biology of Fishes, 2002)

Plankton dynamics: observed and modelled responses to physical conditions in Prince William Sound, Alaska - David L. Eslinger; R. Ted Cooney; C. Peter Mcroy; Alison Ward; Thomas C. Kline; E. Paul Simpson; Jia Wang; Jennifer R. Allen (Fisheries Oceanography, 2001)
Plankton populations in Prince William Sound, Alaska, exhibited pronounced seasonal, annual and longer‐period variability in composition and standing stock in response to physically influenced differences in nutrient availability, and possibly currents that modify local biomass by exchanges with water from the bordering Gulf of Alaska. During springs in which early, strong physical stratification developed, intense, short‐lived phytoplankton blooms occurred. These blooms had relatively short residence times in the water column. In contrast, during springs in which slower, weaker stratification developed, phytoplankton blooms were prolonged and took longer to peak. These slower blooms prolonged the period of phytoplankton production, prolonged interaction with the springtime grazing community and led to the incorporation of more organic matter into pelagic food webs. A coupled biological‐physical simulation of plankton production was used to examine the implications of seasonally varying air and mixed‐layer temperatures, surface winds and incident light on the timing, duration, annual production and standing stock of plankton. Our modelling results reproduced the observed characteristics of the springtime production cycle, and the magnitude of zooplankton stocks for the period 1992–97 but not for 1981–91. These results suggest that for most of the 1990s, bottom‐up influences on nutrient supplies controlled levels of primary consumers, whereas for the 11 years before that, other unknown factors dominated this process. We present the results of a comprehensive, multiyear study of relationships between plankton and physical limitations, and a retrospective analysis of earlier conditions to explore the possible causes for these differences.

Telescoped porphyry Cu-Mo-Au mineralisation, advanced argillic alteration and quartz-sulphide-gold-anhydrite veins in the Thames District, New Zealand - R. Brathwaite; M. Simpson; K. Faure; D. Skinner (Mineralium Deposita, 2001)

The Importance of Nitrogen Oxides for the Exceedance of Critical Thresholds in the Nordic Countries - M. Johansson; R. Suutari; J. Bak; G. Lövblad; M. Posch; D. Simpson; J.-P. Tuovinen; K. Tørseth (Water, Air, & Soil Pollution, 2001)

Aircraft Measurements of Dimethyl Sulfide (DMS) Using a Whole Air Sampling Technique - I. J. Simpson; J. J. Colman; A. L. Swanson; A. R. Bandy; D. C. Thornton; D. R. Blake; F. S. Rowland (Journal of Atmospheric Chemistry, 2001)

Differential Control of Head Blight Pathogens of Wheat by Fungicides and Consequences for Mycotoxin Contamination of Grain - Duncan R. Simpson; Gillian E. Weston; Judith A. Turner; Philip Jennings; Paul Nicholson (European Journal of Plant Pathology, 2001)

Phytoplankton distribution and survival in the thermocline - Jonathan Sharples; Mark C. Moore; Tom P. Rippeth; Patrick M. Holligan; David J. Hydes; Neil R. Fisher; John H. Simpson (Limnology and Oceanography, 2001)
Observations of the vertical structure of density, concentrations of chlorophyll a and nitrate, and turbulent dissipation rates were made over a period of 25 h in a well‐stratified shelf region in the Western English Channel, between neap and spring tides. Maximum turbulent dissipation at the base of the thermocline occurred almost 5 h after maximum tidal currents. This turbulence aids phytoplankton growth by supplying bottom‐layer nutrients into the subsurface chlorophyll maximum but reduces phytoplankton concentrations in the thermocline by mixing cells from the base of the subsurface maximum into the bottom mixed layer. The turbulent dissipation observations were used to estimate an average nitrate flux into the thermocline of 2.0 (0.8‐3.2, 95% confidence interval) mmol m −2 d −1 , which is estimated to have been capable of supporting new phytoplankton growth at a rate of 160 (64–256) mg C m −2 d −1 . Turbulent entrainment of carbon from the base of the subsurface biomass maximum into the bottom mixed layer was observed to be 290 (120–480) mg C m −2 d −1 . This apparent excess export from the chlorophyll maximum is suggested to be a feature of the spring‐neap cycle, with export dominating as the tidal turbulence increases toward spring tides and erodes the base of the thermocline. The observed rate of carbon export into the bottom mixed layer could account for as much as 25% of the gross annual primary production in stratifying shelf seas. Such turbulent losses, combined with grazing losses and low light levels, suggest that phytoplankton need to be highly adapted to environmental conditions within the thermocline in order to survive.

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Transgenic mice for the preparation of puromycin-resistant primary embryonic fibroblast feeder layers for embryonic stem cell selection - Elizabeth R. Linnell; Charles P. Lerner; Kevin A. Johnson; Craig A. Leach; Thomas R. Ulrich; William C. Rafferty; Elizabeth M. Simpson (Mammalian Genome, 2001)

Rhizogenesis in Forsythia×intermedia and Syringa vulgaris ; application of a simple internode experimental system - T. R. Marks; S. E. Simpson (Plant Cell Reports, 2000)

Components of organic phosphorus in soil extracts that are hydrolysed by phytase and acid phosphatase - J. E. Hayes; A. E. Richardson; R. J. Simpson (Biology and Fertility of Soils, 2000)

Estimating normal and pathological dynamic responses in cerebral blood flow velocity to step changes in end-tidal pCO2 - D. M. Simpson; R. B. Panerai; D. H. Evans; J. Garnham; A. R. Naylor; P. R. F. Bell (Medical & Biological Engineering & Computing, 2000)

Interaction of explant type and indole-3-butyric acid during rooting in vitro in a range of difficult and easy-to-root woody plants - Tim R. Marks; Sally E. Simpson (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Ultrasound for the Visualization and Quantification of Tumor Microcirculation - F. Stuart Foster; Peter N. Burns; David H. Simpson; Stephanie R. Wilson; Donald A. Christopher; David E. Goertz (Cancer and Metastasis Reviews, 2000)

A comparative transcript map and candidates for mutant phenotypes in the Tyrp1 (brown) deletion complex homologous to human 9p21-23 - Eleanor H. Simpson; Ruth Suffolk; Julia A. Bell; Siobhán A. Jordan; Dabney K. Johnson; Pat R. Hunsicker; Jack S. Weber; Monica J. Justice; Ian J. Jackson (Mammalian Genome, 2000)

Susceptibility of Broccoli Cultivars to Bacterial Head Rot: In Vitro Screening and the Role of Head Morphology in Resistance - D. Darling; R. Harling; R.A. Simpson; N. McRoberts; E.A. Hunter (European Journal of Plant Pathology, 2000)

Genomic organisation of the human chordin gene and mutation screening of candidate Cornelia de Lange syndrome genes - M. Smith; S. Herrell; M. Lusher; L. Lako; C. Simpson; A. Wiestner; R. Skoda; M. Ireland; T. Strachan (Human Genetics, 1999)

Genomic organisation of the human chordin gene and mutation screening of candidate Cornelia de Lange syndrome genes - M. Smith; S. Herrell; M. Lusher; L. Lako; C. Simpson; A. Wiestner; R. Skoda; M. Ireland; T. Strachan (Human Genetics, 1999)

Characteristics of rural dust events shown to impact on asthma severity in Brisbane, Australia - S. Rutherford; Emma Clark; Grant McTainsh; R. Simpson; Charles Mitchell (International Journal of Biometeorology, 1999)

Geochemistry of an arsenic anomaly in St. Elizabeth, Jamaica - G. Lalor; R. Rattray; P. Simpson; M.K. Vutchkov (Environmental Geochemistry and Health, 1999)

Salinity and fish effects on Salton Sea microecosystems: zooplankton and nekton - Cheryl M. Hart; Maria R. González; E. Paul Simpson; Stuart H. Hurlbert (Hydrobiologia, 1998)

Salinity and fish effects on Salton Sea microecosystems: benthos - E. Paul Simpson; Maria R. González; Cheryl M. Hart; Stuart H. Hurlbert (Hydrobiologia, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Recovery of benthic communities at Macquarie Island (sub-Antarctic) following a small oil spill - S. D. A. Smith; R. D. Simpson (Marine Biology, 1998)

On the role of ?hot towers? in tropical cyclone formation - J. Simpson; J. B. Halverson; B. S. Ferrier; W. A. Petersen; R. H. Simpson; R. Blakeslee; S. L. Durden (Meteorology and Atmospheric Physics, 1998)

Agrobacterium-mediated transformation of Amaranthus hypochondriacus: light- and tissue-specific expression of a pea chlorophyll a/b-binding protein promoter - A. E. Jofre-Garfias; N. Villegas-Sepúlveda; J. L. Cabrera-Ponce; R. M. Adame-Alvarez; L. Herrera-Estrella; J. Simpson (Plant Cell Reports, 1997)

Partial purification and characterisation of an aromatic amino acid aminotransferase from mung bean (Vigna radiata L. Wilczek) - R. M. Simpson; H. M. Nonhebel; D. L. Christie (Planta, 1997)

Why do some females reject males? The molecular basis for male-specific graft rejection - D. M. Scott; I. E. Ehrmann; P. S. Ellis; P. R. Chandler; E. Simpson (Journal of Molecular Medicine, 1997)

Polypedilum digitifer Townes andPolypedilum griseopunctatum (Malloch) (Diptera, Chironomidae): Redescription of adult males with a description and separation of the immature stages - Annelle R. Soponis; Karl W. Simpson (Aquatic Ecology, 1992)

Restriction site polymorphism in genes encoding type 2 but not type 1 gonococcal IgA1 proteases - M. H. Mulks; D. A. Simpson; R. J. Shoberg (Antonie van Leeuwenhoek, 1987)

Effect of time of inoculation with potato leafroll virus on development of net necrosis and stem-end browning in potato tubers - F. E. Manzer; D. C. Merriam; R. H. Storch; G. W. Simpson (American Journal of Potato Research, 1982)

Mount elgon bat virus: A hitherto undescribed virus from Rhinolophus hildebrandtii eloquens K. Anderson - D. Metselaar; M. C. Williams; D. I. H. Simpson; R. West; F. A. Mutere (Archives of Virology, 1969)

Penobscot: A new variety of potato with leafroll resistance and high solids - G. W. Simpson; R. V. Akeley (American Journal of Potato Research, 1964)

Report of editorial committee - Arthur Hawkins; Ora Smith; A. Frank Ross; R. E. Webb; G. W. Simpson; J. C. Campbell (American Journal of Potato Research, 1959)